Constitutive activation of TGF-β receptor type I promotes cortical and cancellous bone formation in adult mice - Tipthanan Chotipinit; Parichart Toejing; Chinnatam Phetkong; Somyoth Sridurongrit; Asada Leelahavanichkul; Julia F. Charles; Sutada Lotinun (PLoS ONE, 2026)
Transforming growth factor β (TGF-β) is a pluripotent cytokine that plays a pivotal role in regulating bone remodeling. In this study, we investigated the skeletal phenotype of 24-week-old transgenic female mice expressing a constitutively active TGF-β receptor type I ( T β RI ) under the control of inducible Mx1-Cre promoter. Poly(I:C) injection was used to induce expression of T β RI to generate Mx1;T β RI CA mice. In Mx1;T β RI CA mice, serum calcium levels were increased, while parathyroid hormone (PTH) levels were decreased. Micro-computed tomography (μCT) analysis revealed a significant increase in cancellous and cortical bone volume in femurs and mandibles of Mx1;T β RI CA mice compared to wild type mice. Histomorphometric analysis confirmed that this enhanced bone volume was associated with an increased number of osteoblasts and a reduced number of osteoclasts. Constitutive T β RI activation resulted in increased alkaline phosphatase and mineralization in primary cultures, while osteoclast cultures from Mx1;T β RI CA mice formed decreased TRAP positive osteoclasts compared to wild-type mice. Furthermore, qPCR analysis demonstrated upregulation of osteoblast differentiation markers, including Runx2 , Sp7 , Alpl , Col1a1, and Ptch2 , while osteoclast-related genes such as Ctsk and Acp5 were downregulated in both femoral and mandibular bone in vivo . Similarly, osteoblast-related genes were increased in Mx1;T β RI CA osteoblasts, whereas osteoclast-related genes were decreased in Mx1;T β RI CA osteoclasts in vitro . Mx1;T β RI CA mice had increased microindentation. These results suggest that constitutive activation of TGF-β signaling promotes bone formation by stimulating osteoblast number while suppressing osteoclast number. This study highlights the important role of TGF-β in bone remodeling and homeostasis and may provide potential therapeutic targets for T β RI -associated bone diseases.